2011
DOI: 10.1016/j.jval.2011.08.407
|View full text |Cite
|
Sign up to set email alerts
|

PMS21 Differences in Cost-of-Illness and Quality of Life Between Rheumatoid Arthritis and Ankylosing Spondylitis in South Korea

Abstract: OBJECTIVES:To estimate and compare cost-of-illness (COI) and health-related quality of life (HRQOL) of rheumatoid arthritis (RA) and ankylosing spondylitis (AS) in South Korea. METHODS: Patients with RA (nϭ196) and AS (nϭ191) were surveyed by face-to-face interviews at the Rheumatology Clinic of Seoul National University Hospital. Direct costs [medical costs (treatment, drug, private physiotherapy, traditional Chinese medicine, other alternative medicine), non-medical costs (travel, dietary supplements, auxili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The abstract by Pumford et al 239 was excluded, as the full publication by Wade et al 240 reported on the same study. The abstract by Lee et al 241 was excluded as a more recent full publication of the study (Lee et al 242 ) reported that a non-UK valuation set was used. Joore et al 243 was also excluded, as primary data were reported in Van Tubergen et al 244 A further three studies were excluded because the manuscripts were in a language other than English.…”
Section: Data Sharing Statementmentioning
confidence: 99%
“…The abstract by Pumford et al 239 was excluded, as the full publication by Wade et al 240 reported on the same study. The abstract by Lee et al 241 was excluded as a more recent full publication of the study (Lee et al 242 ) reported that a non-UK valuation set was used. Joore et al 243 was also excluded, as primary data were reported in Van Tubergen et al 244 A further three studies were excluded because the manuscripts were in a language other than English.…”
Section: Data Sharing Statementmentioning
confidence: 99%